High Resolution Wide Swath SAR Imaging - System Performance and Influence of Perturbations - Gebert, Nicolas; Krieger, Gerhard; Moreira, Alberto (International Radar Symposium, 2005)
The displaced phase centre (DPC) technique enables a wide swath SAR with high azimuth resolution. In classic DPC systems, pulse repetition frequency (PRF), sensor velocity and antenna length underlie a stringent timing requirement to ensure uniform sampling of the synthetic aperture. This constraint can be overcome by the use of a reconstruction algorithm, which enables a recovery of the unambiguous azimuth (Doppler) spectrum also in case of a non-uniform sampling. This paper illustrates the principle of the reconstruction and explains its limitations and the impacts on the ambiguity suppression. The potential of the algorithm when applied to DPC systems like TerraSAR-X with its split receive antenna is demonstrated and the benefits resulting from th e additional receive aperture regarding swat h width and resolution are pointed out. Further on, the impact of additive and phase noise on the reconstruction and its sensitivity against these perturbations are shown.
DLR Import::2019-04-03